High School Students' Critical Thinking Skills through the Development of a Popular Book on Coastal Biology - Muhammad Zaini; Muhammad Arsyad (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The introduction of the potential of coastal biology as a local treasure is important for the general public and students. This study aims to describe the critical thinking skills of high school students through the development of a popular book on coastal biology. This study focuses on small group testing of the Tessmer development research design. The popular book on coastal biology was implemented at Abdul Kadir High School Penyipatan District Tanah Laut Regency, South Kalimantan Province. The research subjects were three students of grade XII. Critical thinking skills are divided into several aspects according to Facione. The instrument used is student worksheet based on popular books on coastal biology. Data is calculated based on weight, then expressed as percent (%) according to the terms of 76-100% (very good), 51-75% (good), 26-50% (quite), <25% (less). The results showed that five aspects of students' critical thinking skills including interpretation, analysis, evaluation, inference, and self-regulation were in good category, and the skills of doing analysis had increased. On the other hand, the skill of explaining has not shown any improvement.Abstrak Pengenalan potensi biologi pesisir sebagai kekayaan lokal penting bagi masyarakat umum dan siswa. Penelitian ini bertujuan untuk mendeSkripsikan keterampilan berpikir kritis siswa SMA melalui pengembangan buku popular biologi pesisir. Penelitian ini fokus pada uji kelompok kecil dari desain penelitian pengembangan Tessmer. Buku populer biologi pesisir diimplementasikan di SMA Abdul Kadir Kecamatan Penyipatan Kabupaten Tanah Laut, Provinsi Kalimantan Selatan. Subjek penelitian adalah tiga orang siswa kelas XII. Keterampilan berpikir kritis dibagi dalam beberapa aspek menurut Facione. Instrumen yang digunakan berupa LKPD berdasarkan buku popular biologi pesisir. Data dihitung berdasarkan bobot, kemudian dinyatakan dengan persen (%) sesuai dengan ketentuan 76-100% (baik sekali), 51-75% (baik), 26-50% (cukup), <25% (kurang). Hasil penelitian menunjukkan lima aspek keterampilan berpikir kritis siswa meliputi interpretasi, analisis, evaluasi, inferensi, dan pengaturan diri memperoleh kategori baik, dan keterampilan melakukan analisis mengalami peningkatan. Sebaliknya, keterampilan melakukan eksplanasi belum menunjukkan perbaikan.